2022
DOI: 10.1084/jem.20210390
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FGF receptor blocks adaptive resistance to RET inhibition in CCDC6-RET–rearranged thyroid cancer

Abstract: Genetic alterations in RET lead to activation of ERK and AKT signaling and are associated with hereditary and sporadic thyroid cancer and lung cancer. Highly selective RET inhibitors have recently entered clinical use after demonstrating efficacy in treating patients with diverse tumor types harboring RET gene rearrangements or activating mutations. In order to understand resistance mechanisms arising after treatment with RET inhibitors, we performed a comprehensive molecular and genomic analysis of a patient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…1a ). Western blot analysis of these cells revealed that selpercatinib substantially decreased RET phosphorylation at Tyr905, an activating autophosphorylation 16 , 41 , 42 , and phosphorylation of ERK1/2 and AKT, the key downstream effectors of RET 16 , while increasing expression of the cyclin-dependent kinase inhibitor p27 KIP1 but decreasing p21 CIP1 expression (Supplementary Fig. 1b, c ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1a ). Western blot analysis of these cells revealed that selpercatinib substantially decreased RET phosphorylation at Tyr905, an activating autophosphorylation 16 , 41 , 42 , and phosphorylation of ERK1/2 and AKT, the key downstream effectors of RET 16 , while increasing expression of the cyclin-dependent kinase inhibitor p27 KIP1 but decreasing p21 CIP1 expression (Supplementary Fig. 1b, c ).…”
Section: Resultsmentioning
confidence: 97%
“…Somatic and germline RET mutations leading to constitutive RET activation are also found in cancers, including multiple endocrine neoplasia type 2 A and 2B (MEN2A and MEN2B) syndromes and familial medullary thyroid carcinoma (MTC) 14 , 15 . Upon activation, RET promotes various cellular processes, including cell growth, proliferation, and survival, mainly through the mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK), the phosphatidylinositol-3 kinase/protein kinase B (AKT) 16 , and the Janus kinase/signal transducer and activator of transcription pathways 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cabozantinib combined with everolimus improves the therapeutic effect of advanced renal cell carcinoma ( 111 , 112 ), which may be a revelation of treatment for patients with RET fusion-positive NSCLC. An important research ( 113 ) result in thyroid cancer, inhibition of FGF receptor blocks adaptive resistance to RET inhibition in CCDC6-RET-rearranged thyroid cancer. This may also be replicated in RET fusion-positive NSCLC.…”
Section: Ret Fusion-positive Nsclc Inhibitorsmentioning
confidence: 99%